Embedded Systems Technologies Using IoT and Wireless Sensor Networks in Semi-Real-Time Modeling - T.A. Samoliuk (Кібернетика та комп'ютерні технології)
Introduction. The Internet of Things (IoT) is a concept for the development of Internet technologies in the direction of automation and exclusion of human participation from most IT infrastructure processes. Embedded systems using IoT and wireless sensor networks or simply embedded IoT systems are characterized by the presence of communication with cloud online services, the presence of connection components, in particular IoT gateways. The operation of embedded IoT systems requires the configuration of a cloud environment for data management, the design of user interfaces, and final testing. The article conducts research on the analysis of existing wireless sensor networks, their advantages and disadvantages, and prospects for further development. Research on the hardware and software necessary for the functioning of embedded Internet of Things systems is conducted. A description of the semi-real-life modeling of the healthcare system for chronically ill patients using embedded IoT systems technologies is provided. The purpose of the paper is describe the methodology and criteria for selecting hardware and software tools for effective use in embedded systems technologies using IoT and wireless sensor networks, which, in turn, allows using these results in semi-real-time modeling of various systems, for example, a healthcare system for chronic patients. Results. The conducted studies confirm the need to use the above tools for effective selection and application of software and hardware tools required in embedded systems using IoT and wireless sensor networks. In particular, their application in the healthcare system for chronic patients. Conclusions. According to the Global Enterprise Spending Management Panel on the Internet of Things, total enterprise spending in the IoT sector may reach $525 billion by 2027. This will be facilitated by the development of the level of technology. In particular, due to the availability of inexpensive hardware with low power consumption. For example, RFID sensors and tags, wireless networks and new cellular networks have high bandwidth necessary for the operation of embedded IoT systems. The article analyzes the technologies of embedded systems using IoT and wireless sensor networks. Field of application: development of embedded IoT systems and their implementation in various areas of life, in particular in the healthcare of chronically ill patients. The article proves that the main goal of embedded systems using IoT and wireless sensor networks is to make our lives more convenient and safe.